China's Military Increase: A Security Dilemma In Asia Pacific - Mufidah Fariani; Badrus Sholeh (Mandala: Jurnal Ilmu Hubungan Internasional, 2020)
This research seeks to show how theories and concepts can explain the rise in China's military and its impact on the Asia Pacific. Through the lens of theory and concept, this paper will also show what causes China to increase its military and why this is a security dilemma for the Asia Pacific. This paper uses the theory of Offense and Defense and also the concept of Security Dilemma. Offense and Defense Theory is intended to explain how the balance between offense and defense in the Asia Pacific region occurs so that it does not cause significant conflict in the Asia Pacific Region. The Security Dilemma concept is used to analyze the impact of China's rising military making the Asia Pacific countries a security dilemma. By using these theories and concepts, it is produced that if Defense is more dominant than Offense, then war will be avoided here, which plays the role of Offense, namely China and Asia Pacific countries play Defense. But China's behavior also cannot be separated from its country's history and position. So, China and the Asia Pacific region have contributed to the offense-defense balance and security dynamics in the Asia Pacific region.